Mythological Thinking and Philosophy - Vladimirovich, Kondratiev Konstantin (International Journal of Criminology and Sociology, 2022)
The article's primary purpose is to analyze the problems of the emergence of philosophy against the background of myth and the correlation of mythical and philosophical styles of thinking. The author substantiates the question of myth theories that do not consider the bearer's inner conviction of mythological thinking in the absolute reality of events and characters described in myths. The main features of the myth as the most ancient form of social consciousness are revealed: absolute subjective certainty, anonymity, which is expressed in an unconscious type of authorship, as well as a specific explanatory function, the essence of which is to implement the solution for a cognitive task before this task itself can be set and consciously formulated. Myth cannot be considered pre-scientific thinking, as an early form of folk art, or as primitive forms of religious worship. The crisis of mythology, which consists of its inability to perform its explanatory function, in turn, generates three new types of social consciousness: epic and other types of the poetry of personal authorship, religious teachings as a system of dogmas and organized cult actions, propagated by the prophets and supported by the priests, and philosophical thinking as a form of conscious intellectual creativity, the reliability of the results of which is supported by the personal wisdom of its author.